Being doll : a study of youngness & oldness at interface - Pavlik-Malone, Lisa (Cambridge Scholars Pub., 2013)
In this second volume, following Dolls & Clowns & Things, the author once again explores the symbolic relationship between the self and the object. This time, however, the possible fundamental role of cognitive consonance, characterized here as the ability of the mind to integrate opposing ideas into a single expanded understanding of Self, is studied in terms of how it might relate to the following three categories of intuitive experience. One, my physical object, in which consonance or ""who ...